AKIBAT HUKUM PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN PENERBITAN KARTU KREDIT DI BNI 46 MEDAN - ARIEF FREDY KURNIAWAN HAREFA (PREMISE LAW JURNAL, 2015)
The use of credit cards is one form of a loan agreement between the consumer as the customer / debtor to the bank as creditor. Type of applied research is to use the research to the method of writing the normative approach (normative legal research). The results of the study and discussion of the issuance of the credit card agreement explains in BNI 46 Medan meet the principle of freedom of contract and does not meet the principle of balance. The agreement meets the principle of freedom of contract because the credit card issuance agreement is 'take it or leave it contract' so that the parties are free to accept or not accept the agreement offered. Then the conclusion publishing agreement kedit card does have the principle of freedom but does not have the balance principle of contract. Then doctrine for someone dependent on agreement whose contents are not read and do not understand the true doctrine of the subjection of the will of the public (de leer van de Algemene wilsonderwerping). As a result of the application of the law of the exoneration clause in the agreement that issued the credit card issuance BNI 46 field such agreement does not meet the principle of balance though the parties were bound by the agreement have the right and the reciprocal agreements in connection with the issuance of a credit card and based on this it can be said the issuance of the credit card agreement is null and void due to non-fulfillment of the third and fourth terms of the provisions of Article 1320 of the Civil Code which is an objective requirement of an agreement. Ways to resolve disputes as a result of the use of the exoneration clause in the agreement that the issuance of credit cards issued BNI 46 field by means of deliberation and consensus and if the path can not resolve the problem then carried through the completion of the local District Court.   Keywords: Clause, exoneration, Publishing, Credit Card